Reproductive Performance in a Selected Sample of Dairy Farms in Una-Sana Canton, Bosnia and Herzegovina - Adis Softic; Adam Dunstan Martin; Eystein Skjerve; Nihad Fejzic; Teufik Goletic; Aida Kustura; Erik Georg Granquist (Veterinary Medicine International)
Background. The production of milk and dairy products and their placement on the market represent a constant profit for the farmers/producers in Bosnia and Herzegovina (BH). The profitable operation of the dairy farms is influenced by the reproductive performance of the lactating animals. This study assessed individual animal reproductive characteristics in selected dairy farms and described their reproductive performance indicators. Results. The median age at first insemination was 493 days (5th–95th percentile range 429–840), while the age at first calving was 802 days (5th–95th percentile range 708–1168). The median pregnancy proportion at first insemination was 40% (5th–95th percentile range 17–62), while the cumulative pregnancy rate calculated at day-60, day-80, day-100, and day-120 showed that approximately 64% of all pregnancies happened before day-120. The calculated interservice intervals showed that approximately 69% of the repeat breeding animals came back to the oestrus in the period of 18 to 24 days. This is an indication of very good oestrus detection in selected dairy farms. The mean number of services per pregnancy was 2.61 (range 1–12). The median calving-to-first-insemination interval was 62.5 days (5th–95th percentile range 16–408). The calving-to-conception interval was 101 day (5th–95th percentile range 36–506). Finally, the calving interval was 385 days (5th–95th percentile range 329–773). Conclusions. There is a need for an organised, regular, and more comprehensive recording system for the reproduction of dairy cattle among dairy farms in Una-Sana Canton. The calculated reproductive measures indicated an undulant trend in reproductive performance among selected dairy farms in Una-Sana Canton. Knowing the apparent reproductive indicators described in this study, the farmers and veterinary authorities may identify and correct areas in their management that contribute to the reproductive underperformance.